2021
DOI: 10.1177/10935266211001308
|View full text |Cite
|
Sign up to set email alerts
|

Lineage Switch in an Infant B-Lymphoblastic Leukemia With t(1;11)(p32;q23); KMT2A/EPS15, Following Blinatumomab Therapy

Abstract: We report a 6 month-old infant girl with t(1;11)(p32;q23), KMT2A/EPS15-rearranged B-acute lymphoblastic leukemia (B-ALL) that was refractory to traditional ALL-directed chemotherapy. Following administration of blinatumomab, she experienced lineage switch from B-ALL to acute myeloid leukemia (AML). Myeloid-directed chemotherapy resulted in clearance of AML by flow cytometry, though a residual CD19+ B-ALL population persisted (0.14%). Following bridging blinatumomab, the patient achieved B-ALL and AML remission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…The current designation of mixed phenotype acute leukemia (MPAL) includes a specific category for MLL -r, as well as BCR-ABL+ leukemia, because of their prevalence in this mixed lineage group [ 46 , 47 ]. Consistent with this concept of high lineage plasticity in MLL-r leukemia, evasion of CD19-targeted immunotherapy through relapse with myeloid markers has been reported under treatment with blinatumimab [ 20 27 , 32 ] or treatment with CD19 CAR T cells ( Table 1 ) [ 10 , 18 , 30 , 31 , 33 ]. Loss of not only the CD19 cell surface protein but complete loss of all B-lineage markers and acquisition of a myeloid phenotype characterizes these cases ( Table 1 ).…”
Section: Lineage Identity and Plasticity In Mll -R B-allsupporting
confidence: 57%
See 1 more Smart Citation
“…The current designation of mixed phenotype acute leukemia (MPAL) includes a specific category for MLL -r, as well as BCR-ABL+ leukemia, because of their prevalence in this mixed lineage group [ 46 , 47 ]. Consistent with this concept of high lineage plasticity in MLL-r leukemia, evasion of CD19-targeted immunotherapy through relapse with myeloid markers has been reported under treatment with blinatumimab [ 20 27 , 32 ] or treatment with CD19 CAR T cells ( Table 1 ) [ 10 , 18 , 30 , 31 , 33 ]. Loss of not only the CD19 cell surface protein but complete loss of all B-lineage markers and acquisition of a myeloid phenotype characterizes these cases ( Table 1 ).…”
Section: Lineage Identity and Plasticity In Mll -R B-allsupporting
confidence: 57%
“…In some reports, clonal relationships between the B-ALL and the AML are discussed through detailed characterization of the MLL rearrangement as well as immunoglobulin heavy chain rearrangements ( Table 1 ) [ 18 , 23 , 26 , 32 , 33 ]. Recent single-cell genomics data suggest that pre-existing myeloid-primed B-ALL cells could be the source of such relapses (see Figure 2 ) [ 49 ].…”
Section: Lineage Identity and Plasticity In Mll -R B-allmentioning
confidence: 99%
“…A review of the past 8 years since the FDA's initial approval of blinatumomab identified 33 reported cases, 17 with blinatumomab and 16 with an anti‐CD19 CAR‐T cell therapy (Table 1). 5–19 The median [IQR] number of prior CRs was 1 [1, 2] (among those reported) with time to LS occurring within 12 months in 90.9% of patients. Of significance, the KMT2A‐rearrangement was implicated in 81.8% of cases—88.2% with blinatumomab and 75% with a CAR‐T immunotherapy.…”
Section: Reference [Year] Age Prior No Of Crs Unique Molecular Charac...mentioning
confidence: 99%
“…As many patients can show circulating myeloid blasts after treatment, whether due to marrow regeneration or in response to growth factor therapy, pathologists and/or hematologists interpreting flow cytometry may be tasked with determining whether the detection of circulating myeloid blasts represents a reactive finding or the early signs of a myeloid lineage‐switch. To this end, it should be noted that a majority of reported KMT2A r lineage‐switched myeloid blasts show a myelomonocytic or outright monocytic immunophenotype at relapse, a trait that may provide a diagnostic clue in this setting 6 –8,10,15,22,23,22(p) . As such, if myeloid‐oriented MRD assays are to be used at the time of evaluation, a tube capable of evaluating immature monocytes, with markers such as CD64, CD11b, CD14, CD4, CD34, HLA‐DR, CD33, and CD45 may be of utility 24 …”
Section: Lymphoid To Myeloid Switchmentioning
confidence: 99%
“…The frequency of a lineage switch at relapse was initially estimated at 6.7% using FAB lineage assignment criteria; however, this number likely represents an overestimate when considering the advancement in immunophenotypic evaluation of leukemias since 1984 coupled with the more stringent lineage criteria employed by the current WHO classification system 1–3 . Most cases of lineage transformation involve a switch from acute lymphoblastic leukemia (ALL) to acute myeloid leukemia (AML) 2,4–15 . Moreover, leukemic lineage switch is more frequently observed in infant leukemia and in young patients with gene rearrangements of the epigenetic and transcriptional regulator, lysine methyltransferase 2A, ( KMT2A ; formerly MLL1 ), and often occurs immediately after or even during induction chemotherapy 5,16 .…”
Section: Lymphoid To Myeloid Switchmentioning
confidence: 99%